Ropeginterferon alfa‐2b in patients with genotype 1 chronic hepatitis C: Pharmacokinetics, safety, and preliminary efficacy. Issue 8 (10th July 2021) - Lin, Hsien‐Hong; Hsu, Shih‐Jer; Lu, Sheng‐Nan; Chuang, Wan‐Long; Hsu, Chao‐Wei; Chien, Rong‐Nan; Yang, Sien‐Sing; Su, Wei‐Wen; Wu, Jaw‐Ching; Lee, Tzong‐Hsi; Peng, Cheng‐Yuan; Tseng, Kuan‐Chiao; et al.
ABSTRACT: Background and Aim: Ropeginterferon alfa‐2b (P1101) is a novel long‐acting mono‐PEGylated recombinant proline interferon (IFN) conjugated to a 40 kDa branched polyethylene glycol (PEG) chain at its N‐terminus, allowing every‐two‐week injection. It received European Medicines Agency and Taiwan marketing authorization for the treatment of polycythemia vera in 2019 and 2020, respectively. This phase 2 study aimed to evaluate the pharmacokinetics, safety, and preliminary efficacy of ropeginterferon alfa‐2b as compared with PEG‐IFN‐α2a in patients with chronic hepatitis C virus genotype 1 infection. Methods: One hundred six treatment naive patients were enrolled in this phase 2 study and randomized to four treatment groups: subcutaneous weekly PEG‐IFN‐α2a 180 μg (group 1), weekly ropeginterferon alfa‐2b 180 μg (group 2), weekly ropeginterferon alfa‐2b 270 μg (group 3), or biweekly ropeginterferon alfa‐2b 450 μg (group 4) plus ribavirin for 48 weeks. Results: After multiple weekly administration, serum exposure (AUC0‐τ ) in ropeginterferon alfa‐2b 180 μg was approximately 41% greater and the accumulation ratio of 2‐fold greater than PEG‐IFN‐α2a 180 μg. The incidences of flu‐like symptoms were 66.7% (18/27), 53.3% (16/30), 55.0% (11/20), and 48.3% (14/29), anxiety were 14.8% (4/27), 6.7% (2/30), 0%, and 0%, and depression were 25.9% (7/27), 13.3% (4/30), 0%, and 3.4% (1/29), for groups 1–4, respectively. Two grade 2 of 3 depression were noted in PEG‐IFN‐α2a arm, but none in ropeginterferon arms. The SVR24 rates were 77.8% (21/27), 66.7% (20/30), 80% (16/20), and 69% (20/29), respectively. Conclusions: Ropeginterferon alfa‐2b showed longer effective half‐life and superior safety profile than PEG‐IFN‐α2a. Biweekly injection of ropeginterferon alfa‐2b will be studied in larger viral hepatitis patient population. Abstract : Ropeginterferon alfa‐2b (P1101) is a novel mono‐PEGylated recombinant proline‐interferon alfa‐2b with a 40 kDa branched polyethylene glycol (PEG) chain conjugated predominantly at its N‐terminus. Ropeginterferon alfa‐2b showed longer effective half‐life and superior safety profile than pegylated interferon alfa‐2a. Ropeginterferon alfa‐2b will be developed to fill the gap of the need for chronic hepatitis B treatment and is exceptionally needed for chronic hepatitis D.